Inovace praktické výuky multimediální projekcí z mikroskopické anatomie. Dýchací systém - Pomfy, Mikuláš (MEFANET report, 2008)
The project aimed at creation of a multimedia classroom has been realized by the Institute of Histology and Embryology. It provides application of electronic teaching components to medical curricula courses. A multimedia projector connected with a notebook is available in addition to light microscopes enabling presentation of organ structures in microscopic anatomy. Multimedia projection seems to be an optimal way of upgrading microscopic anatomy teaching, at the same time it can supply the lectures. Concurrently, the project allows for build-up of a virtual microscopic sections library to be used in general histology, as well as in microscopic anatomy. A database of virtual microscopic sections from organ systems will be accessible to the students by e-mail address creation.
Keywords: Education, Medical; Computer Simulation; histologie; Slovakia; Histology; Multimedia; Slovenská republika; anatomie; Medical Informatics Applications; využití lékařské informatiky; studium lékařství; Anatomy; počítačová simulace; multimédia